2015
DOI: 10.4238/2015.april.27.18
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 gene polymorphisms in North Chinese patients with pulmonary tuberculosis

Abstract: ABSTRACT. Pulmonary tuberculosis (PTB) remains one of the most important infectious diseases worldwide. Several studies have suggested that genetic factors may affect the susceptibility to PTB, but the specific genes involved have not been fully characterized. The gene for monocyte chemoattractant protein 1 (MCP-1) has been linked to an increased risk of tuberculosis in some Mexican and Korean populations. To explore the role of the MCP-1 gene in the susceptibility to PTB in a North Chinese population, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Recently, accumulating evidences demonstrated that MCP-1 genetic variations within the regulatory regions could make patients susceptible to certain inflammation-related diseases, infection and sepsis by altering MCP-1 expression levels. [ 32 34 ] Furthermore, a number of studies demonstrated that inhibition or specific antagonism of MCP-1 could decrease the septic response and are beneficial to survival in mouse models of sepsis. [ 35 37 ] These results confirmed that MCP-1 played an important role in the pathomechanisms of immune dysregulation and maybe a promising potential therapeutic target for correcting the immune disorder of severe trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidences demonstrated that MCP-1 genetic variations within the regulatory regions could make patients susceptible to certain inflammation-related diseases, infection and sepsis by altering MCP-1 expression levels. [ 32 34 ] Furthermore, a number of studies demonstrated that inhibition or specific antagonism of MCP-1 could decrease the septic response and are beneficial to survival in mouse models of sepsis. [ 35 37 ] These results confirmed that MCP-1 played an important role in the pathomechanisms of immune dysregulation and maybe a promising potential therapeutic target for correcting the immune disorder of severe trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Many infectious diseases and inflammatory disorders are associated with MCP-1-2518A>G polymorphism [18] , [24] , [25] , [26] . In another study, like the present study, this polymorphism was investigated in SARS-CoV-2 infection using the GWAS method.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were used for genomic DNA extraction via DNA extraction kit (Tiangen, Beijing, China). The amplification of rs1024611 SNP [ 19 ] was accorded with the previous study using polymerase chain reaction (PCR). Finally, PCR products were sequenced by ABI 3730XL analyzer (Applied Biosystems, Foster City, CA).…”
Section: Methodsmentioning
confidence: 99%